PEMBUATAN DAN PEMANFAATAN PUPUK ORGANIK CAIR (POC) DARI SAMPAH ORGANIK RUMAH TANGGA DI KELURAHAN TAMA POLE, MUARA JAWA, KUTAI KARTANEGARA - M. Rizky Wardani; Imam Rohadi; Maria Angelina Permata (PROSIDING SEMINAR KIMIA, 2025)
Waste management remains a persistent challenge in the Tama Pole Village. One of the initiatives to address this issue is by utilizing organic waste to produce liquid organic fertilizer (LOF). This activity aimed to transform household organic waste into LOF and apply it in the cultivation of family medicinal plants (TOGA). The method used was the production of LOF from household organic waste through a fermentation process assisted by Effective Microorganisms 4 (EM4). The microorganisms in EM4 are fermentative microbes that degrade mocromolecular compounds (carbohydrates, lipids, and proteins) in organic waste into smaller molecule compounds that can be easily absorbed by plants as nutrients. The result of the production of LOF was obtained are in the form of a yellowish-brown liquid with a characteristic fermentation aroma. This indicates that the macromolecular compounds in the organic waste has been decomposed into simpler compounds such as sugars, alcohols, fatty acids, amino acids, simple corboxylic acids, and inorganic ions, wich are rich in soil nutrients (N, P, K, and other micro nutrients). Based on these results, it can be concluded that LOF from household organic waste was successfully produced and applied in the cultivation of TOGA. Keywords: Family Medicinal Plants, Health, Liquid Organic Fertilizer, Organic Waste, Soil Nutrients.